ЗНАМЕТО НА РЕПУБЛИКА МАКЕДОНИЈА ВО АМБЛЕМИТЕ НА АРМ (1992-2018) / THE FLAG OF THE REPUBLIC OF MACEDONIA ON ARM EMBLEMS (1992–2018) - Trajce Trajkov (Македонски хералд - Macedonian Herald, 2019)
A chronological and a colorful presentationof those emblems of ARM unitsand commands used during 1992–2018which contain the flag of the Republic ofMacedonia. Legal norms—regulationsgoverning the subject matter—and on thebasis of collections material, a total of 43different ARM emblems are describedand presented. Keeping in mind that independentMacedonia changed its flag twice(1992 and 1995), changes were made tothe army emblems in accordance with theemerging reality The first emblem of the ARMfrom 1992, which represented the then state flag,inherited from Socialist Republic of Macedonia,and is considered a collector’s item since it wasin use for only four months; then the first generalARM emblems for formal and official uniformsof 1993; rare emblems of ARM units from the1990s; the 2005 Engineer Regiment emblemswith the Sun of Kutleš; as well as existing emblemsof ARM commands and units introducedin 2012. A common unifying thread for all ofthem is the representation of the flag of the Republicof Macedonia.